PENGARUH KARAKTERISTIK PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO DALAM LAPORAN KEUANGAN INTERIM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Dwi Urip Wardoyo; Alifia Salsabila; Dewi Wulan; Nadya Amelia Ramadhanti; Vela Belleza (CV. Ulil Albab Corp, 2022)
The purpose of this research is to provide empirical evidence about company characteristics such as firm size, profitability, and leverage, and then corporate governance mechanisms such as board size, and audit committee that affect corporate risk disclosure in interim financial reports. The statistical method used to test the hypotheses is multiple regression analysis. The population of this research is listed mining firms on IDX 2017-2018. Thirty-three mining firms listed on IDX in 2017-2018 were chosen as samples. To explain the effect between the variables, agency and signaling theories were used. And then, corporate risk disclosure was measured with the content analysis method. These results of this research show that firm characteristics attributes (firm size, probability, and leverage) and corporate governance (board of commissioner’s size and audit committee) have a significant positive effect on corporate risk disclosure in interim financial reports.